2005
DOI: 10.1128/jcm.43.2.966-969.2005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Foot-and-Mouth Disease Virus Type C of Indian Origin

Abstract: Comparison of nucleotide sequences of the partial 1D region of foot-and-mouth disease type C viruses of Indian origin with those of European, South American, and Southeast Asian viruses revealed that the Indian viruses form a distinct genotype. The vaccine strain C IND/51/79 belongs to this genotype and may be a prototype strain of this genotype

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…However, the low level of sequence divergence observed in this study is comparable to that observed in C 1 subtype strains from Europe, which showed very little change from 1953 to 1989 [4]. The absence of significant sequence divergence in type C strains has also been reported in India [25]. The apparently static evolution in the European subtype C 1 strains was attributed to multiple re-introductions of vaccine strains into the field through laboratory escapes or improperly inactivated vaccines.…”
Section: Discussionsupporting
confidence: 75%
“…However, the low level of sequence divergence observed in this study is comparable to that observed in C 1 subtype strains from Europe, which showed very little change from 1953 to 1989 [4]. The absence of significant sequence divergence in type C strains has also been reported in India [25]. The apparently static evolution in the European subtype C 1 strains was attributed to multiple re-introductions of vaccine strains into the field through laboratory escapes or improperly inactivated vaccines.…”
Section: Discussionsupporting
confidence: 75%
“…In the region, other subtypes circulated; in India, not only serotype O (Mason et al., 2003; Saeed et al., 2009) but also serotype C (Nagendrakumar et al., 2005) and serotype A (Nagendrakumar et al., 2009) have been isolated with both O and A isolated frequently and recently. Serotype Asia 1 has also been identified in India (Valarcher et al., 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Because of very long borders (with lengths that are unfenced), animals may move between these countries without restriction, leading to the uncontrolled spread of FMDV. Considerable work regarding the molecular epidemiology of FMDV in southern Asia has already been published (Hemadri et al., 2002; Tosh et al., 2002; Knowles and Samuel, 2003; Knowles et al., 2005, 2009; Nagendrakumar et al., 2005; Klein et al., 2007, 2008; Mohapatra et al., 2008; Rana and Bagchi, 2008; Schumann et al., 2008; Valarcher et al., 2009). However, there is an ongoing need to determine the identity of circulating FMDV strains in the region to ascertain their origin(s).…”
Section: Results Of Fmdv Identification In the 58 Samples Examinedmentioning
confidence: 99%